The Effectiveness of the Implementation of Merdeka Curriculum Physical Learning Strategies on Motivation and Student’s Achievement - Arizona, Wendy; Rahman, Andi; Putri, Siti Ayu Risma (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2024)
The study focused on increasing student motivation and academic achievement in physical education, sports, and health (PJOK) subjects at PGRI Kundi Junior High School by implementing Merdeka curriculum-based strategies. Using a descriptive qualitative approach, data was gathered through in-depth interviews, observations, and questionnaires involving 10 eighth-grade students, 2 teachers of physical education, sports, and health subjects, and the school principal. The data analysis revealed that both teachers and students experienced improved learning motivation and academic outcomes. The collaborative approach between teachers and students fostered a more relevant and dynamic learning environment, further enhancing the quality of education. The effectiveness of this strategy highlights the potential for more contextual and relevant learning methods that align with the demands of the Merdeka curriculum. By engaging students in a more flexible, student-centered curriculum, their enthusiasm and commitment to learning are significantly heightened. The positive changes in teaching methods and assessments have not only improved students’ physical skills but also supported their overall academic performance. This approach has proven particularly beneficial in fostering a deeper connection between students and their learning processes. Teachers play a crucial role in maintaining this momentum by continually adapting their strategies to the evolving needs of their students. The success of the Merdeka curriculum in this context suggests that similar approaches could be effective in other subjects as well. Ultimately, this model presents a promising avenue for enhancing educational outcomes in diverse learning environments.